Penguatan Kelembagaan Unit Informasi Layanan Sosial Dalam Pelayanan Kepada Keluarga Dengan Anggota ODGJ Di Desa Jambenenggang, Kabupaten Sukabumi - Supriatna, Ecep; Rahmi, Kus Hanna; Andayani, Rini Hartini Rinda; Susilawati, Susilawati; Vonika, Nike; Fahrudin, Adi (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
The "Institutional Strengthening of the Social Service Information Unit (UILS)" activity was held on 4-6 July 2024 in Jambenenggang Village, Sukabumi Regency, thanks to the collaboration of the Faculty of Psychology, Bhayangkara University and Poltekesos Bandung. The purpose of this activity is to increase capacity and strengthen the role of UILS in providing responsive mental health services, especially for families with members of People with Mental Disorders (ODGJ). This activity was attended by 25 participants who were UILS administrators and volunteers, and included training on basic mental health knowledge, crisis management techniques, and early psychological support. This training aims to enable participants to identify early signs of mentaldisorders and carry out early interventions, preventing more serious conditions. In addition to increasing individual capacity, institutional strengthening is carried out by discussing organizational governance, social service access strategies, and efficient referral mechanisms to advanced mental health services. Practical sessions were also held, with simulations of providing psychological first aid in emergency situations to ensure that participants not only understand the theory but also have practical skills. Group discussions were also held to explore the problems faced by ODGJ families and find joint solutions, facilitating the sharing of experiences in providing mental health services. The results of this activity are expected to strengthen the role of UILS as the main source of support in the community, as well as improve the quality of mental health services in Jambenenggang Village, making it a model for other areas.